The Relationship Between the Returns and Volatility of Stock and Oil Markets in the Last Two Decades: Evidence from Saudi Arabia - Alsharif, Mohammad (International Journal of Economics and Financial Issues, 2020)
Using daily data from 2000 to 2019, this study examines the sensitivity of Saudi market returns and volatility to changes in oil prices. This study employs the threshold general autoregressive conditional heteroskedastic in mean model (TGARCH-M) and three multivariate general autoregressive conditional heteroskedastic (MGARCH) models. Overall, it is found that oil price changes have a significant positive impact on Saudi stock market returns. More, there is a positive relationship between the volatility of stock and oil markets, and this positive relationship has increased significantly in the last decade. Thus, Saudi Arabia is recommended to diversify its economy away from oil income to enhance their stock market efficiency and stability. Keywords: Saudi Arabia, Tadawul, Oil, Volatility, TGARCH-M, MGARCH JEL Classifications: C32, E44, G12 DOI: https://doi.org/10.32479/ijefi.9869